Long term urban wastewater irrigation drives zinc bioaccumulation and health risks in contaminated vegetables - Shahzad Akhtar; Ahmed Muneeb; Zafar Iqbal Khan; Iram Saba; Kafeel Ahmad; Mohammad Faisal; Abdulrahman A. Alatar; Muhammad Iftikhar Hussain; Rana Muhammad Zubair; Muhammad Nadeem (Scientific Reports)
Abstract Zinc (Zn) is a vital plant nutrient, and its judicious use is required for plant growth, development, and productivity. This study assessed the uptake of zinc in kitchen vegetables after being treated with wastewater (WW), canal water (CW), or tube well water (TW). Samples of water, soil and edible portions of selected vegetables (Spinacia oleracea, Brassica campestris, Coriandrum sativum, and Mentha spicata) were collected randomly from three ecological sites (Sargodha, Sahiwal, and Shahpur) in Punjab, Pakistan. The results revealed that the Zn concentrations in water (0.7757–1.4521 mgL−1), soil (5.36–41.3 mgkg−1 ) and vegetables (4.11–24.86 mgkg−1) were statistically significantly different (p < 0.01) with increasing Zn concentration in the order: TW < CW < WW, emphasizing the potential risks associated with using wastewater for irrigation. A strong positive correlation existed for the zinc concentrations across all the sites, treatments and between soil and vegetables. The transfer factor (TF) analysis value indicated (0.46–1.21) the bioaccumulation of Zn in the vegetables. The single pollution index (SPI) values ranged from 0.12 to 0.93, with the maximum health risk detected in S. oleracea, suggesting a significant level of contamination risk, and the enrichment factor (EF) (0.2–0.54) revealed moderate–to-high-level enrichment in the soil. The geoaccumulation index (Igeo) (-3.628–0.692) suggested that soils were unpolluted in TW and CW and moderately polluted at WW-irrigated sites. The health risk index (HRI) (0.06–0.38) and target hazard quotient (THQ) (0.014–0.085) both indicate that the consumers of these vegetables are not toxic or at risk. It is suggested that wastewater alone is inappropriate for vegetables because it leads to continuous Zn buildup in the soil, which may be detrimental. To prevent excessive accumulation of Zn in the food chain, regular monitoring is needed.